Prevalence of Helicobacter Pylori in Patients Undergoing Gastroduodenoscopy in Birat Medical College Teaching Hospital - Kafle, Neeta; Singh, Mrinalini; Sinha, Amrita; Sedhain, Sapana; Bhattarai, Soorya (Birat Journal of Health Sciences, 2025)
Introduction: Helicobacter (H) pylori is a very common infection that causes chronic and active gastritis, peptic ulcer, duodenal ulcer and associated with increased risk of developing gastric cancer and mucosa associated lymphoid tissue lymphoma. H pylori as a definite carcinogen, hence it is important to understand the geographic burden of disease for its ultimate clinical and infrastructural management. Objective : To find the prevalence of Helicobacter pylori in patients undergoing gastroduodenoscopy. Methodology : A descriptive cross sectional study was conducted among 126 patients during a period of six months from Jan 2023 to July 2023. All patients that underwent gastroduodenosopy followed by biopsy was included in the study. Patients taking anti H pylori treatment within two weeks prior evaluation, patients with prior gastric surgery, upper gastrointestinal bleed due to varices, diagnosed malignant ulcers and biopsies of esophagus, biopsies containing only necrotic and only ulcerative tissue were excluded from the study. Processed and stained samples were examined by two pathologist and reported using modified Sydney system. Data obtained was analyzed using SPSS version 23. Result: A total of 126 patients underwent gastroduodenoscopy during the study period. It was seen that Helicobacter pylori infection rate was 22.2% with highest prevalence in patients aged 31-40 years (28.6%) Upper abdominal pain was the most common symptom (68.3%) of cases with 25.6% of helicobacter pylori positive rate in this group. Conslusion : The prevalence of H pylori is 22.22% reinforcing its role in gastroduodenal pathology.